Hak Anak dalam Konstitusi di Indonesia - Andi Tenri Padang; Sofyan; Gunawan, Muhammad Safaat (Jurnal Al Tasyri'iyyah, 2023)
ABSTRACT The main issues in this research are how the legal protection of children's rights is regulated in the Indonesian constitution, what is the state's responsibility for the constitutional rights of children in Indonesia. The results of this study indicate that the protection of children's rights in the Indonesian constitution of the 1945 Constitution has been outlined both in writing and impliedly in Article 28 B paragraph 2, Article 28 D paragraph 1, and Article 34 paragraph 1 which explicitly recognizes the existence of children's rights. which must be protected both to sustain life, grow and develop as well as protection from various violence and acts of care. The State of Indonesia has carried out various obligations and responsibilities to maintain and provide protection for children's constitutional rights through normative arrangements, special programs and the establishment of various state institutions capable of carrying out child protection specifically including the Ministry of Women and Children's Empowerment, the Commission Child Protection, the Police Women and Children Protection Unit and Non-Governmental Organizations Special for Children. Keywords: Children's Rights, Constitution in Indonesia